Major determinants for the selecting antithrombotic therapies in patients with nonvalvular atrial fibrillation in Japan (JAPAF study). Issue 2 (11th August 2016) - Kusakawa, Koichi; Harada, Kouji H.; Kagimura, Tatsuo; Koizumi, Akio
Abstract: Background: Oral anticoagulants (OACs) can help prevent stroke in patients with nonvalvular atrial fibrillation (NVAF). The aim of this study was to characterize the use of OACs other than direct thrombin inhibitors (DTIs) for NVAF. Methods: Patients with NVAF taking antithrombotics other than DTIs were enrolled in this cross‐sectional study. Patient demographics and medication history were collected, and the patients were classified as taking antiplatelet monotherapy (AP), anticoagulant monotherapy (AC), or combination therapy (AP+AC). OAC users were also stratified as naïve (N; initiated within 6 months), switcher (S; switched within 6 months), or prevalent user (P; continued for >6 months). Results: A total of 3053 patients (AP, 216; AC, 2381; AP+AC, 456) from 268 sites were enrolled from 2012 to 2013. Significant differences were observed in CHADS2 scores (AP/AC/AP+AC: 2.0/2.1/2.7, P <0.0001), angina complications (20.1/8.6/32.1, P <0.0001), myocardial infarction (5.1/2.8/18.1, P <0.0001), prothrombin time–international normalized ratio (PT–INR) (−/2.00/1.94, P =0.0350), and others. There were 2831 OAC users (N, 328; S, 213; P, 2290). Significant differences were observed in history of bleeding (N/S/P: 2.4/9.4/4.5, P <0.001), PT–INR (1.83/2.01/2.00, P <0.0001), and others. Conclusions: Patients taking AP+AC had higher CHADS2 scores than those taking an AP or AC alone. Additionally, the combination therapy (AP+AC) was preferred in patients with cardiovascular comorbidity. Changes in AC regimens were not influenced by CHADS2 scores or complications but influenced by history of bleeding. These characteristics were thus identified as major factors affecting the selection of antithrombotic regimens other than DTIs in patients with NVAF.